THE EFFECTS OF ENGLISH SONGS ON THE SEVENTH GRADE STUDENTS’ PRONUNCIATION ACHIEVEMENT IN SMP SRIJAYA NEGARA PALEMBANG - Adelia Yusmita; Nike Angraini (Global Expert: Jurnal Bahasa dan Sastra, 2017)
This study was conducted in order to know the effectiveness of pronunciation achievement based on English songs strategy. This study applied a quasi-experimental research design, specifically non-equivalent control group design. The objectives of the study were to find out whether or not (a) there was significant improvement of students’ pronunciation achievement after being taught by using English songs (b) there was significant difference of pronunciation achievement between the students who were taught by using English songs and those who were not. The population was all the seventh grade students in SMP Srijaya Negara Palembang. This research, the researcher used purposive sampling. The sample was divided into two samples, there were 30 samples for experimental group and 30 samples for control group. The data were collected by using t-test (Paired Samples t-test and Independent Samples t-test). The findings showed that English songs strategy signifcantly improve the students’ pronunciation achievement (T=36.947). In addition, there was significant difference in pronunciation achievement between the students who were taught through English songs strategy and those who were not (T=12.663). Based on this study, it is found that the use of English songs in teaching English is effective to improve the students’ pronunciation and very beneficial for the students in order to facilitate them in learning English. Based on this finding, it is suggested that English songs in teaching English can be recommended for the English teachers.Key word: effect, English songs, pronunciation